Medical, Dental, and Nursing Students' Knowledge about Early Childhood Oral Health Care - Wasan Yousef Al-Hatlani; Sanaa Najeh Al-Haj Ali (MDPI AG, 2019)
Gaps in knowledge of physicians and nurses about early childhood oral health care were reported and are likely due to the poorly focused education on oral health issues; therefore, the purpose of this study was to assess the knowledge level of Qassim University medical, dental and nursing students about early childhood oral health care and its relation to demographic variables, students’ perceived knowledge, satisfaction with their knowledge and interest in further education about the topic. A total of 571 medical, dental, and nursing students received a questionnaire that included demographic questions, questions to assess knowledge level of the students about early childhood oral health care, and questions to assess their perceived knowledge level, satisfaction with their knowledge and interest in further education about the topic. Results of the study revealed that knowledge of dental students was highest (score 7.72 out of 10) followed by nursing students (4.79), and medical students (4.43). Additionally, students with a higher level of perceived knowledge were more likely to score higher. In view of the inadequate knowledge level of medical and nursing students about early childhood oral health care when compared to dental students, improvements in medical and nursing education programs are necessary at Qassim University.